A Simple Sonochemical Synthesis of Nanosized ZnO from Zinc Acetate and Sodium Hydroxide - Zakirov, M. I.; Semen'ko, M. P.; Korotchenkov, O. A. (Journal of Nano- and Electronic Physics, 2018)
An efficient sonochemical route for synthesis of nano sized zinc oxide is reported. The method employs zinc acetate and sodium hydroxide as precursors with isopropyl alcohol as a solvent. As prepared powders were characterized by XRD, SEM and FTIR. These show that the resulting powder is composed of multi-domain crystallites of ZnO wurtzite, zincite and Zn(OH)2. The XRD-measured coherent domain size varies from about 20 to 30 nm, whereas SEM exhibits 200 nm crystallites. The wurtzite phase is found to dominate at sonication times smaller than 30 min. It is also found that the powders produced sonochemically exhibit smaller and narrower size-distributed particles compared to that in hydrothermally prepared powders.